Outdoor Study sebagai Mediasi Pembelajaran Aktif yang Mempengaruhi Berfikir Kritis Peserta Didik - Muhandoyo, Muhandoyo; Kristiawan, Indria (FKIP Universitas Wisnuwardhana, 2020)
This study aims to determine Outdoor Study as an active learning mediation influencing students’ critical thinking. This research was conducted at SDN Slampangerejo Jabung. This research method is quantitative with analysis using Structural Equation Modeling (SEM). Data collection was collected a test technique using LKS, observation and documentation. The results showed that Outdoor Study as an active learning medium influences students' critical thinking. The outdoor study model used is Problem Based Learning (PBL). Through the application of this learning shows the ability to think with several indicators, namely 1) identifying; 2) analytical skills; 3) problem solving skills; 4) conclusion skills; 5) judging skills and 6) evaluating skills.